Application of temperature-responsive HIS-tag fluorophores to differential scanning fluorimetry screening of small molecule libraries - Ronzetti, Michael H.; Baljinnyam, Bolormaa; Itkin, Zina; Jain, Sankalp; Rai, Ganesha; Zakharov, Alexey V.; Pal, Utpal; Simeonov, Anton (Frontiers in Pharmacology, 2022)
Differential scanning fluorimetry is a rapid and economical biophysical technique used to monitor perturbations to protein structure during a thermal gradient most often by detecting protein unfolding events through an environment-sensitive fluorophore. By employing an NTA-complexed fluorophore that is sensitive to nearby structural changes in histidine-tagged protein, a robust and sensitive differential scanning fluorimetry (DSF) assay is established with the specificity of an affinity tag-based system. We developed, optimized, and miniaturized this HIS-tag DSF assay (HIS-DSF) into a 1536-well high-throughput biophysical platform using the Borrelial high temperature requirement A protease (BbHtrA) as a proof of concept for the workflow. A production run of the BbHtrA HIS-DSF assay showed a tight negative control group distribution of Tm values with an average coefficient of variation of 0.51% and median coefficient of variation of compound Tm of 0.26%. The HIS-DSF platform will provide an additional assay platform for future drug discovery campaigns with applications in buffer screening and optimization, target engagement screening, and other biophysical assay efforts.